356 Clinical and Economic Benefits of Cervical Cancer Cotesting With Three- and Five-Year Intervals. (11th January 2018) - Lacey, Michael; Lenhart, Gregory; Miller, Jeffrey; Hilborne, Lee; Pohlman, Scott; Vilalta, Adrian; Troeger, Kathleen; Felix, Juan
Abstract: Objectives: To analyze clinical and economic benefits of cervical cancer screening using cotesting (cytology plus human papillomavirus [HPV] testing) with three- vs five-year intervals. Methods: Previously published economic, epidemiologic, and clinical data (Felix et al. J Women's Health . 2016) demonstrating benefits of cotesting over primary HPV screening were used to develop a health state transition (Markov) cost-utility model with a one-year cycling. A hypothetical cohort of 1 million women receiving cervical cancer screening at either three- or five-year intervals was simulated for 40 years (starting at age 30 years until age 70 years). Outcomes included invasive cervical cancer (ICC) cases, ICC-related deaths, costs (2016 USD), and quality-adjusted life years (QALYs). Comprehensive sensitivity analyses were performed. Results: Model analyses predicted 40% fewer ICC cases with a three-year cotesting interval compared with a five-year interval (57.61 vs 96.51 per 10, 000 women for three- and five-year intervals, respectively). ICC deaths were predicted to be 39% lower (23.06 vs 37.58 per 10, 000 women for three- and five-year intervals, respectively). Results for the three-year interval screening show a lifetime gain of 0.0201 QALYs (23.0084 QALYs vs 22.9883 QALYs for three- and five-year intervals, respectively). The cumulative increase in screening costs for three-year cotesting intervals ($477 per woman over 40 years) was partially offset by cost savings ($114) realized from cervical cancer prevention and reduced treatment cost. The modest net increase in total cost for three-year co-testing intervals ($363) can be considered cost-effective compared with five-year cotesting based on an incremental cost-utility ratio (ΔCost/ΔQALY) of $18, 060 per QALY gained. Conclusions: Cervical cancer cotesting at three-year intervals is predicted to be a cost-effective approach to reducing the number of ICC cases and ICC deaths over currently recommended five-year intervals.